Character strengths: A study of Argentinean soldiers - Cosentino, Alejandro César (2012)
The primary objective of this research was to study the differences in positive traits between military and civilian college students and between cadets in their first and final years at a military academy. Second, the research aimed to study the relations between positive traits and the academic and military performance of cadets in their first and final years, according to the classification of positive traits by Peterson and Seligman (2004). To accomplish these objectives, a sample of university students from a military educational institution and a sample of civilian university students were studied. The instruments used were a 24-item self-report measure of positive traits, a measure of social desirability, and objective scores of academic and military performance. The results generally showed that when age and career stage were held constant, the scores of the military students were higher than the scores of the civilian students across various strengths. Military students reported higher levels of the character strength of spirituality than did civilian students. The relationships between strengths and performance differed for students in their first and final years at the military academy. In particular, cadets with the higher levels of academic or military performance in their last year, i.e., the cadets best adapted to the academy, reported higher levels of the character strength of persistence when compared to low-performing cadets in the same year of study.